Analysis of Management Elements in Antibiotic Inventory Control with EOQ and MMSL Methods at Aisyiyah Bojonegoro Hospital - Pramono Apriawan Wijayanto; Ayun Sriatmi; Sutopo Patria Jati (Borneo Journal of Pharmacy, 2023)
Inventory control is important in managerial activities because it involves investment and is hospitals' most significant expenditure component. The Aisyiyah Bojonegoro Hospital requires a logistics management system that can maintain the safety and effectiveness of the use of drugs for the smooth running of hospital pharmaceutical services in the long term. This analytical observational study analyzes management elements in controlling antibiotic inventory by simulating the Economic Order Quantity (EOQ) and Minimum-Maximum Stock Level (MMSL) methods. Determination of the sample purposively, i.e., 17 types of antibiotic drugs category A from the results of the ABC analysis, with the inclusion criteria being high cost, high volume, clinically important drugs for antibiotic drugs that are included in the 2020 Hospital Formulary and the exclusion criteria are drugs with inadequate supply. The analysis technique used the Mann-Whitney test and the Kruskal-Wallis test. Based on the results of the study, it was concluded that. Applying the EOQ and MMSL methods has been proven to increase the efficiency and effectiveness of the supply of category A antibiotics at Aisyiyah Bojonegoro Hospital.